Geostatistical and geospatial approaches for the characterization of natural resources in the environment : challenges, processes and strategies /: challenges, processes and strategies. (2016) - International Association for Mathematical Geosciences., Conference, (16th) 2014 (New Delhi, India)
No abstract available